Evaluating the social and physical components of leisure and recreational quasi-public spaces in Davao City contributing to place attachment - Reyes, Trisha Jamaica C.; Rosel, Minerva C. (2020)
This study aims to determine the level of place attachment in Davao City?s leisure and recreational quasi-public spaces and to learn how place attachment can be enhanced in these places through design by identifying the social and physical components of a place that significantly contribute to its development. There has been an increase in quasi-public spaces for leisure and recreation in Davao City for the past years.The study was conducted to help promote people-place bond in these places. A total of four leisure and recreational quasi-public spaces were visited in order to gather the needed data through observation, photo documentations, surveys and interviews. The data gathered were then analyzed to identify the social and physical components that significantly contribute to place attachment. The research shows that users do not have a high place attachment in Davao City?s leisure and recreational spaces and the design of these spaces can be enhanced through fromulating design guidelines based on the results of the study. A food park and nightlife hub is proposed that would enhance place attachment and promote people-place bond.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020